Dead but functional liquid nitrogen‐treated umbilical cord mesenchymal stem cells accelerate full‐thickness skin wound healing - Yan Yang; Yuqing Feng; Meirong Hu; Jingxian Deng; Siying Wei; Zhaoyang Wang; Lu Li; Rufei Huang; Yuxin Wang; Yuan Liu; Tao Ye; Yadong Huang (Wiley, 2023)
Abstract Background The direct application of umbilical cord‐derived mesenchymal stem cells (UCMSCs) for promoting skin wound healing and regeneration is challenging due to strict maintenance requirements and unpredictable differentiation results. Methods We developed dead but functional liquid nitrogen‐treated UCMSCs (LNT‐MSCs) by rapidly immersing live UCMSCs (live‐MSCs) in liquid nitrogen. Results The LNT‐MSCs maintained similar cellular structures and surface markers to those of live‐MSCs. We evaluated the therapeutic effects of both live‐MSCs and LNT‐MSCs on full‐thickness skin wound healing in rats. Our results showed that the LNT‐MSCs accelerated wound closure by enhancing the proliferation and migration of skin cells, promoting angiogenesis, and inducing a favourable macrophage phenotype shift. The regenerative healing effect of LNT‐MSCs was comparable to that of live‐MSCs, making them a potential alternative strategy for accelerating wound closure that avoids unpredictable differentiation results and creates a ready‐to‐use cell bank for clinical applications.